ICT services features to support intrinsic value activities for productive ageing - Norisan Abd Karim; Haryani Haron; Wan Adilah Wan Adnan (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Intrinsic values associated with ICT services activities in productive ageing. Given the advances made in ICT services that have been widely used, elderlies need to be equipped with the knowledge in using the services. The lack of ICT usage among elderlies is because of the low motivation to use the ICT applications. This in turn could be due to the lack of intrinsic values associated with the use of ICT applications among elderlies. This study explores further the features of ICT services needed to support intrinsic values activities. Brainstorming sessions is conducted in this study where it involved six ICT experts in order to identify ICT services features to support intrinsic value activities. Intrinsic motivation features are significant features in ICT services to support intrinsic value activities for productive ageing. There are five intrinsic motivation features identified in this research, which are autonomy, competence, relatedness, altruism and curiosity. The ICT services to support intrinsic value activities model comprises of the ICT services characteristics that are transactive, community-based with online communication channels, and incorporated with intelligent agents.